Implementasi Pengasuhan Bahasa Cinta dalam Mengembangkan Kecerdasan Emosional Anak Usia 4-5 Tahun - Hasna Marwah; Enoh; Huriah Rachmah (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Common problems with children's emotional intelligence are caused by parenting and incorrect communication interactions. One aspect that significantly affects children's growth and development is emotional development. The upbringing of love languages is used as an improvement competency for teachers in Raudatul Atfal Al-Mukaromah to improve children's emotional intelligence. In the application of love language parenting, there is a rule where teachers are prohibited from being angry, forbidding, commanding, and pointing at students. This study uses a qualitative approach with a case study method. The purpose of this study is to determine the planning and the implementation of the results of the implementation of love language parenting in developing the emotional intelligence of children aged 4-5 years and find out the supporting factors and inhibiting factors. Based on the findings of the research data, it was concluded that planning emphasizes the process of character education. Love language parenting at RA Al-Mukaromah is carried out in learning activities and parenting training. The results of the implementation of love language parenting on children's emotional intelligence are found in the report on children's learning outcomes. The supporting factor lies in the self-upgrading of the teacher while the inhibiting factor lies in the environment. Teachers use positive words and lighter sentences in the application of love language upbringing Solutions to further improve the effectiveness of love language parenting are: (1) there needs to be a benchmark in love language parenting planning for teachers to see the appropriateness in the application of love language parenting activities (2) the use of media in love language parenting such as visual images pasted in the classroom that show affection, and various emotions (3) the creation of Standard Operating Procedures (SOPs) specifically for love language parenting methods (4) implementation training activities that need to be carried out twice to see the development. Abstrak. Permasalahan umum tentang kondisi kecerdasan emosional anak disebabkan pola asuh dan interaksi komunikasi yang salah. Salah satu aspek yang sangat berpengaruh pada tumbuh kembang anak ialah aspek perkembangan emosional. Pengasuhan bahasa cinta dijadikan kompetensi peningkatan bagi guru di Raudatul Atfal Al-Mukaromah dalam upaya meningkatkan kecerdasan emosional anak. Penerapan pengasuhan bahasa cinta terdapat sebuah aturan dimana guru dilarang untuk marah, melarang, memerintah, dan menunjuk kepada peserta didik. Pada penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Tujuan penelitian ini ialah untuk mengetahui perencanaan pelaksanaan hasil implementasi pengasuhan bahasa cinta dalam mengembangkan kecerdasan emosional anak usia 4-5 tahun, dan mengetahui faktor pendukung serta faktor penghambat. Berdasarkan hasil temuan data penelitian, didapatkan kesimpulan bahwa perencanaannya menekankan pada proses pendidikan karakter. Pengasuhan bahasa cinta di RA Al-Mukaromah dilaksanakan dalam kegiatan pembelajaran dan training parenting. Hasil implementasi pengasuhan bahasa cinta terhadap kecerdasan emosional anak terdapat pada laporan capaian pembelajaran anak. Faktor pendukung terletak pada self-upgrading guru sedangkan faktor penghambat terdapat pada lingkungan. Guru menggunakan kata positif dan kalimat pemantik dalam penerapan pengasuhan bahasa cinta. Solusi untuk lebih meningkatkan efektivitas pengasuhan bahasa cinta ini adalah: (1) perlu adanya tolok ukur dalam perencanaan pengasuhan bahasa cinta terhadap guru melihat kesesuian dalam penerapan pengasuhan bahasa cintakegiatan (2) penggunaan media dalam pengasuhan bahasa cinta seperti gambar visual yang ditempelkan dalam kelas yang menunjukkan kasih sayang, dan macam-macam emosi (3) pembuatan Standar Operasional Prosedur (SOP) khusus untuk metode pengasuhan bahasa cinta (4) pelaksanaan kegiatan training yang perlu dilaksanakan dua kali guna melihat perkembangannya.